2021
DOI: 10.31125/hunhemsire.968858
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of Music Application on Intensive Care Patients: A Systematic Review

Abstract: Bu sistematik derleme ile yoğun bakım hastalarında müzik uygulamasının hastalar üzerindeki fizyolojik ve psikolojik etkilerinin belirlenmesi amaçlanmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
(66 reference statements)
0
6
0
2
Order By: Relevance
“…The results of an experimental study conducted to determine the effect of music on CPAP compliance and agitation levels of patients in need of respiratory support in the COVID-19 intensive care unit were discussed in light of the literature. 3,[14][15][16][17][18]21,22,[29][30][31][32][33][34][35][36][37] The age, sex, education level, marital status, BMI, GCS, CPAP duration, tidal volume and respiratory pressure characteristics of the patients included in the study were similar in the intervention and control groups. The mean age of the patients varied between 60 and 65 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of an experimental study conducted to determine the effect of music on CPAP compliance and agitation levels of patients in need of respiratory support in the COVID-19 intensive care unit were discussed in light of the literature. 3,[14][15][16][17][18]21,22,[29][30][31][32][33][34][35][36][37] The age, sex, education level, marital status, BMI, GCS, CPAP duration, tidal volume and respiratory pressure characteristics of the patients included in the study were similar in the intervention and control groups. The mean age of the patients varied between 60 and 65 years.…”
Section: Resultsmentioning
confidence: 99%
“…17,31,32 In the multi-session music application performed by Dallı et al, 18 the RASS scores of the patients who underwent mechanical ventilation also decreased. A systematic review carried out by Sazak et al, 15 investigating the music intervention in intensive care patients, reported that music positively affected anxiety, sedation, pain and comfort levels in intensive care patients. It has been emphasized that music should be listened to for a minimum of 30 min for physical and psychological effects on the organism.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations